Optimizing Food Cost Management: A Case Study at Patra Cirebon Hotel & Convention - Khodijah Islamiah Marulafau; Palupiningtyas, Dyah; Tri Maryani (International Journal of Educational and Life Sciences, 2024)
This study aims to analyze the factors affecting food cost, measure the influence of these factors on food cost, and formulate strategies to optimize food cost management at Patra Cirebon Hotel & Convention. This research employs a qualitative approach with a case study design. Data were collected through semi-structured interviews, observations, and document analysis. The research participants were those directly involved in food cost management at the hotel. The data were analyzed using thematic analysis techniques. The results show that the factors affecting food cost include food ingredient prices, portion sizes, chefs' ability to process food ingredients, as well as inventory and purchasing control. These factors have an influence on food cost, where ineffective management can lead to a significant increase in food cost. Strategies that can be implemented to optimize food cost management include vendor development, employee training and development, and technology adoption. This research contributes theoretically to the development of hospitality management science and practically to hotel managers in improving operational efficiency. Research limitations and suggestions for future research are also discussed.